Robot Pintar Pengukur Kepuasan Konsumen pada Pusat Perbelanjaan - Muhamad Dwisnanto Putro; Jane Litouw (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2018)
The shopping center generally uses the questionnaire instrument in measuring the level of customer satisfaction services. Processing and presentation of conventional questionnaire data tend to be long and less effective. The problem will be solved by using smart robots to measure consumer satisfaction at shopping centers. This robot has a digital questionnaire module located on the robot's chest and the facial module that is used as a robot expression when the consumer chooses to be satisfied or not with the shopping center service. The digital robot questionnaire module is able to accommodate, store and process customer satisfaction data in statistics. Robotic expression when receiving a choice of consumer satisfaction in the form of happy or disappointed facial expressions combined with a voice expression in the form of thanks to customers who have visited.